Studi Komparasi Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Loyalitas Karyawan PT. Indocement Tunggal Prakarsa Tbk Unit Citeureup Antara Karyawan Generasi X dan Karyawan Generasi Y - Rusdiana, Endang; Mutmainah, Isbandriyati; Putra, Mulyana Gustira (Jurnal EMT KITA, 2025)
The purpose of this study is to examine the impact of the work environment and compensation on employee loyalty at PT Indocement Tunggal Prakarsa Tbk Citeureup Unit, with a comparison of generation X and generation Y employees. This study’s population consists of all employees of PT Indocement Tunggal Prakarsa Tbk Citeureup Unit, and the sample is drawn from that population using the purposive sampling method. The analytical method used is multiple linear regression, with work environment and compensation as independent variables and employee loyalty as the dependent variable. Using 340 respondents, the study found that work environment and compensation variables have a positive and significant impact on employee loyalty at the PT Indocement Tunggal Prakarsa Tbk Citeureup unit, for both generation X and generation Y. Work environment variables have a greater influence on loyalty for generation X compared to generation Y, while the compensation variable has a greater influence on loyalty for generation Y than generation X.